2015
DOI: 10.1111/gcb.12952
|View full text |Cite
|
Sign up to set email alerts
|

Warm temperature acclimation impacts metabolism of paralytic shellfish toxins from Alexandrium minutum in commercial oysters

Abstract: Species of Alexandrium produce potent neurotoxins termed paralytic shellfish toxins and are expanding their ranges worldwide, concurrent with increases in sea surface temperature. The metabolism of molluscs is temperature dependent, and increases in ocean temperature may influence both the abundance and distribution of Alexandrium and the dynamics of toxin uptake and depuration in shellfish. Here, we conducted a large-scale study of the effect of temperature on the uptake and depuration of paralytic shellfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
4
20
0
Order By: Relevance
“…The same trend was previously described by Farrell et al (2015) In contrast, a reduction of nearly 50 % of clearance rates were reported in mussels M.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The same trend was previously described by Farrell et al (2015) In contrast, a reduction of nearly 50 % of clearance rates were reported in mussels M.…”
Section: Discussionsupporting
confidence: 88%
“…Most studies on climate change effects in shellfish have focused on a single driver (e.g. temperature, acidification, salinity) (Anestis et al, 2010(Anestis et al, , 2007Farrell et al, 2015;Fernández-Reiriz et al, 2012). A reduced number of studies addressed the combination of two variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40] Diarrheic Shellfish Poisoning (DSP) Okadoic acids Dinophysis, Procentrum [41] Neurotoxic Shellfish Poisoning (NSP) Brevetoxin Karenia brevis [42] Ciguatera Shellfish Poisoning (CFP) Ciguatoxin Gambierdiscus toxicus [43] the onset of paralysis. Blocking of sodium conductance eventually generates symptoms of numbness, tingling sensation of the oral parts and nausea to the patient.…”
Section: Poisoning Toxin Organismsmentioning
confidence: 99%
“…for emerging risks: rising ocean temperatures impacts metabolism of toxins in oyster Warm temperature acclimation impacts metabolism of paralytic shellfish toxins from Alexandrium minutum in commercial oysters Farrell, 2015. Possibly relevant as seen by TNO experts: nano-and microplastics Ingestion of Nanoplastics and Microplastics by Pacific Oyster Larvae.…”
mentioning
confidence: 99%